Poincare series of the multigraded algebras of SL 2-invariants - Bedratyuk, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Formulas for computation of the multivariate Poincare series P(C_d, z_1, z_2,..., z_n,t) and P(I_d, z_1, z_2,..., z_n), are found, where C_d, I_d, d = (d_1, d_2,..., d_n) are multigraded algebras of joint covariants and joint invariants for n binary forms of degrees d_1, d_2,..., d_n .